Common sense ; The rights of man and other essential writings of Thomas Paine - Paine, Thomas, 1737-1809. (New York : Signet Classic, 2003)
Presents eighteenth-century political philosopher Thomas Paine's treatises "Common Sense" and "Rights of Man" and selections from "The Crisis," "The Age of Reason," and "Agrarian Justice," and provides a further reading list.
Common sense -- The crisis (selections) -- The rights of man (selections) -- The Age of Reason -- Agrarian justice (selections).
Originally published: New York : New American Library, 1969.
Includes bibliographical references (p. 379-380).
Adult
Keywords: Political science -- Early works to 1800.